(untitled) (Global Journal of Science Frontier Research, 2018)
Pesticides are harmful and toxic in nature. They are used for vegetable protection against pest attack. The present study aimed to determine the level of Organophosphorus and Pyrethroid residues in vegetables (Solanum macrocarpum L. and Lactuca sativa L.) Thirty one vegetable samples (16 samples of Solanum macrocarpum L. and 15 samples of Lactuca sativa L.) from four vegetable farms were collected. The samples were cleaned up before the extraction was performed. Analysis was then processed using the QuEChERS method. Residue analysis was performed using a GC-PFPD for Organophosphorus residues and GC-ECD for Pyrethroid residues. MedCalc Statistical Software version 15.0. was used for the statistical analysis. The results revealed that most of the samples are contaminated by Pyrethroid and Organophosphorus residues.